Maternal Genistein Intake Mitigates the Deleterious Effects of High-Fat Diet on Glucose and Lipid Metabolism and Modulates Gut Microbiota in Adult Life of Male Mice - Zhou, Liyuan; Xiao, Xinhua; Zhang, Qian; Zheng, Jia; Deng, Mingqun (Frontiers in Physiology, 2019)
Adverse early-life exposures program increased risk of chronic metabolic diseases in adulthood. However, the effects of genistein supplementation in early life on metabolic health in later life are largely unclear. Our objective was to investigate whether maternal genistein intake could mitigate the deleterious influence of a maternal high-fat diet on glucose and lipid metabolism in offspring and to explore the role of gut microbiota in mediating the transgenerational effects. C57BL/6 female mice were fed either a high-fat diet (HF), high-fat diet with genistein (0.6 g/kg diet) (HFG) or normal control diet (C) for 3 weeks before pregnancy and throughout pregnancy and lactation. The male offspring had ad libitum access to normal chow diet from weaning to 24 weeks of age. Then the content of inguinal subcutaneous adipose tissue (SAT) and epididymal visceral adipose tissue (VAT) were weighed. Glucose tolerance test (GTT), the level of serum insulin and lipid profiles were analyzed. The caecal contents were collected for 16s rDNA sequencing. The results showed that maternal genistein intake could significantly reduce blood glucose levels during GTT, fasting insulin levels, VAT mass and serum triglyceride levels as well as increase high-density lipoprotein cholesterol in adult male offspring. Significant decrease of germs from the Tenericutes phylum and enrichment of Rikenella as well as SCFA (short-chain fatty acid)-producing bacteria, including Alloprevotella, Odoribacter and Clostridium XlVa, in offspring of genistein fed dams might play crucial roles in the improvement of glucose and lipid metabolism. Overall, early-life genistein intake attenuated the harmful effects of maternal HF on metabolism in adult offspring and the protective effects were associated with the alterations in gut microbiota, which provides new evidence and targets for mitigate the poor effects of adverse early-life exposures on metabolic health in later life.